Komodifikasi Pantai Bali Lestari sebagai Daya Tarik Wisata di Kecamatan Pantai Cermin - Fizha Khairi; Hidayat Amsani; Ibnu Hajar Damanik (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This study aims to determine the form commodification of Bali Lestari Beach as a tourist attraction in the District of Pantai Cemin. Commodification is carried out by adopting Balinese culture and renewal of Bali Lestari Coast facilities, as evidenced by this commodification, can increase the number of tourist visits. The research method used is a qualitative method with an ethnographic approach, data collection techniques using participatory observation and interviews. The results of this study explain the form of commodification carried out on the Bali Lestari beach by changing the beach brand from Indah to Bali. Then adopt Balinese culture such as traditional Balinese architecture, Balinese arches, paintings of puppet figures, statues and polished saput, which are made in such a way as to be identical to the nuances on the island of Bali. To get the appropriate commodification, the manager renewed and added several supporting facilities such as, water games, photo spots, prayer rooms, bathrooms and restaurants. The increase in visitors creates new jobs for the surrounding community, many of whom are shifting jobs from farming and fishing to traders on the beach. In order to get a permit to sell in this coastal area, the manager charges a low fee to the merchant to be paid. Government participation is also very necessary to develop the Bali Lestari Coast.